Determinan konsumsi mie instan pada mahasiswa Universitas Sriwijaya - Vera Utami; Yayi Suryo Prabandari; Susetyowati Susetyowati (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Determinants of instant noodles consumption among students in Sriwijaya universityPurposeThis study aimed to explore the factors that influence the instant noodle consumption among students in Sriwijaya university. MethodsThis research was a qualitative study with phenomenological approach. Data were collected through in-depth interviews with 20 informants. The sampling technique was purposive sampling. The data collection was conducted from June-September 2015.ResultsThis study showed that individual factors are the most influential factors, including time constraints, taste, aroma, and prices which were supported by the social environmental factors, including the pattern of family relationships and patterns of friendship. Physical environmental factors included easy access and sufficient availability of instant noodles and macro environmental factors including the lack of campus policies, social norms in the society as well as the advertising effect on the consumption of instant noodles with new flavors. ConclusionStudents receive advice about diet from educational promotional efforts through seminars and social media.